Penyuluhan Penghijauan Melalui Pembuatan Eco-Pot Dan Edukasi Pembuatan Pupuk Kompos Di Desa Kemiri Kecamatan Kaloran - Listiyono Budi; Fatur Satria; Zulfa Aliya; Ilham Cahyo Saputro; Rafi Satria Cahaya Putra; Achifatul Kumayah (Universitas Negeri Semarang, 2026)
This activity is filled with three activities, namely socialization of the importance of greening, making EcoPots from plastic bottle waste, and making compost from rice straw and goat manure. This activity aims to increase awareness of the importance of greening and the importance of preserving the environment from an early age. The target of this activity is the 5th grade students of MI Nurul Falah located in Pringtali Hamlet, Kemiri Village, Kaloran District. The methods used in this activity are lectures and demonstrations. Lectures are carried out by delivering material in the form of understanding greening, the importance of greening, benefits, and the correct way to plant trees. The demonstration method is carried out by practicing making Eco-Pots and making compost using raw materials of rice straw and goat manure which are widely available around Kemiri Village, then added with EM-4, rice husks, granulated sugar, and water. The results of this activity are compost and pots from decorated plastic bottles and then used to plant plants in the school environment.